Potensi Kebakaran Hutan di IUPHHK-HT PT Finnantara Intiga Kabupaten Sintang Provinsi Kalimantan Barat - Bambang Hero Saharjo; Muhammad Yodhi Muhtady (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
The forest fire potential based studied on rainfall and fire source of forest fire also forest fire controlling. The research was conducted from February to May 2016 in IUPHHK-HT PT Finnantara Intiga Sintang Distric Province Kalimantan Barat in the village of Sejirak and Ratu Damai. The objectives of this research are to analyze the level of vulnerability forest fire based on rainfall during 5 years, to analyze the source of forest fire and analyze the efforts of forest fire controlling in IUPHHK-HT PT Finnantara Intiga Sintang Distric Province Kalimantan Barat. The result showed that the average of yearly rainfall at 5 years was 3 659 mm. It can be categtorized into not fine front. While the largest potency of fire sources is come from the society in Sejirak village and Ratu Damai village, almost 80% the society in that village still using fire to do land clearing. Forest fire controlling in IUPHHK-HT PT Finnantara Intiga Sintang includes prevention, suppression and extinguishing. Keyword : Rainfall, forest fire, Source fire, Sintang, West Kalimantan